Decoration in religious architecture of the eighteenth century in the south eastern part of Central Europe - Botica, Dubravka (Array, 2014)
When researching the religious architecture of the Baroque era it is essential to consider each building as a Gesamtkunstwerkand to include research into technique, materials and decoration. Architects often designed ornaments, J.L. von Hildebrandt being the most prominent example. There are several examples of the interweaving of architectural design and interior ornament in the buildings of the South Eastern part of Central Europe ; for example, in historical Styria and the North Western part of Croatia. The churches constructed by J.G. Stengg’s building workshop from Graz, and those in the North Western part of Croatia which were influenced by it, often share identical motifs between stuccowork, the decoration of altars, and architectural forms: a 1730s motif of rhomboidal mesh with rosettes, for example, can be found simultaneously in stucco decorations on the vault of the church in Pokupsko and as ornaments on the capitals of churches at Styria (at Rogatec, for example, or on the façade of the Barmherzigen-Brüder church in Graz) ; while a type of irregular window frame, the so-called ‘Casula-Fenster’, can be found in the aforementioned churches and, at the same time, as a painting frame on the altars designed by Stengg himself (at the monastery church in Rein, and in Pokupsko). These examples of corresponding motifs in architecture and ornament emphasize the need for more holistic research. Such an approach highlights how these churches were the result of a type of organization within the building workshops of the period, in which decorators were employed as co-workers. This important aspect of Baroque architectural design has been neglected by traditional art-historical studies of the Central European area. This paper addresses this position by offering a new examination of some of key eighteenth-century Baroque interiors in this region.